METODE ULAR TANGGA BERPENGARUH TERHADAP PENGETAHUAN ANEMIA PADA REMAJA PUTRI DI SMA MUHAMMADIYAH 5 YOGYAKARTA - Aliya Puspita Rizwani; Enny Fitriahadi (Jurnal Ilmiah Kebidanan Imelda, 2025)
Anemia is a disorder characterized by a reduction in hemoglobin levels in the bloodstream or red blood cells, leading to an impaired capacity of red blood cells to transport oxygen to tissues. Anemia in female adolescents is attributed to malnutrition, particularly deficiencies in iron and folic acid, with insufficient knowledge being a contributing factor. The prevalence of anemia among female adolescents in Yogyakarta City Regency is 29.51% (2,844 people). One method that can improve adolescent girls' understanding of anemia is through media-based teaching, particularly utilizing the snakes and ladders game as a teaching instrument. This study aims to determine the effect of the snakes and ladders approach on the knowledge level of female adolescents at SMA (Senior High School) Muhammadiyah 5 Yogyakarta. This research employed a quasi-experimental design featuring a pre-post-test with a control group. The sampling method employed total sampling, obtaining 86 female students as participants.The Mann-Whitney test was employed for data analysis. The study's results suggested that the snakes and ladders approach significantly influenced the knowledge level of female adolescents on anemia at SMA Muhammadiyah 5 Yogyakarta, as evidenced by the active participation of respondents in the learning process, with a p value = 0.000 <0.05. The snakes and ladders technique is an excellent, engaging, and interactive educational tool that enhances female adolescents' understanding of anemia. Female adolescents are encouraged to proactively seek information regarding anemia, particularly its causes, symptoms, and preventive measures, to prevent future anemia-related problems.